Pilot study of 'Scissorhands' technique for gastric endoscopic submucosal dissection using novel gel and endoscopic scissors in a porcine model (with video). Issue 3 (31st October 2013) - Khashab, Mouen A.; Saxena, Payal; Sharaiha, Reem; Messallam, Ahmed; Akshintala, Venkata S.; Singh, Vikesh K.; Lennon, Anne Marie; Canto, Marcia I.; Kalloo, Anthony N.; Pasricha, Pankaj J.
Abstract : Background and Aim: Endoscopic submucosal dissection (ESD) is a complex procedure and is associated with significant risks. The aims of this pilot study were to study feasibility and procedural times of gastric ESD using a novel gel and endoscopic scissors in a porcine model. Methods: Simulated 3‐cm gastric submucosal lesions were created in a porcine model. Subsequently, viscous gel was injected into the created bleb. A needle knife was used to create an initial incision when needed. Endoscopic scissors were then used for circumferential incision around the simulated submucosal lesions. The inserted coil (i.e. submucosal lesion) was then removed. The submucosal surface was carefully examined for signs of injury. Procedural times were recorded. Results: ESD was carried out in four consecutive pigs using the 'Scissorhands' technique. A small submucosal incision was created a using needle knife in the first pig and electrocauterywas not used in the remaining three pigs. Circumferential incision using the scissors was done successfully in all pigs. Submucosal dissection was not required in any case. 'Auto‐dissection' of created lesions by the gel was noted to be complete in all cases. Inserted coils were noted in the submucosal space during all experiments and were removed. All lesions were successfully resected en bloc. The mean procedure time was 19 min (range 13–22 min). Conclusion: The combined technique of endoscopic scissors for circumferential incision and viscous gel for submucosal dissection permitted easy, safe and efficient gastric ESD. Electrocautery may be avoided and its consequent adverse events (e.g. perforation).